Selected Legal Aspects of National Security and Critical Infrastructure Protection in the European Union with Particular Reference to the Polish National Legislation - Ocieczek, Grzegorz (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
In the current geopolitical scenario, ensuring national security and the protection of critical infrastructure seem to be key elements for upholding the proper functioning of a state and, consequently, the safety of its citizens. This paper addresses issues related to the protection of critical infrastructure in territory of the European Union (EU). Particular attention is paid to issues regarding legal solutions to ensure the security of EU member states. EU directives concerning the immunity of critical entities (CER) and issues related to ensuring a high level of cybersecurity in the territory of the EU (NIS 2) are discussed. The paper is divided into several main parts, which, in addition to the above-mentioned issues regarding the legal aspects of critical infrastructure protection, also address security (e.g. types and divisions) and terrorism (e.g. the most important legal acts aimed at counteracting this very dangerous phenomenon is indicated). This study also discusses the European Security Strategy (2020–2025) and its most important objectives regarding the security of critical infrastructure, anti-terrorism, cybersecurity, and the protection of public spaces. Regarding national security, the paper discusses the various national security strategies from 1990 to the present in Poland, showing that the strategies pay particular attention to the changing approaches to security, the assessment of the current situation at the time and threats involved, and the increasing need to ensure the protection of critical infrastructure. The publication ends with conclusions and postulates regarding the need to ensure national security and increase the protection of critical infrastructure. Keywords: Critical infrastructure, national security, terrorism, cybersecurity, national security strategies, European security strategies.